2016
DOI: 10.14359/51689158
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Shear Behavior of High-Strength Concrete Structural Walls

Abstract: High-strength concrete (HSC) walls having compressive strength of approximately 100 MPa (14,500 psi) were tested under cyclic lateral loading to investigate their shear behavior. The parameters included were height-to-length ratio of the walls, vertical and horizontal web reinforcement ratios, and the effects of boundary elements in the form of flanges. The experimental results show that shorter walls exhibit greater shear strength than taller walls. Both vertical and horizontal web reinforcements contribute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 1 publication
(1 reference statement)
0
26
1
Order By: Relevance
“…This may be attributed to the adoption of FSAM theory in the model. The other validation of cracking patterns for rectangular RC walls is presented in Figure 11, which shows the comparison of the cracking patterns for specimen J4 [14]. It can be observed that the model is able to predict the global cracking patterns of the specimen.…”
Section: Cracking Patternsmentioning
confidence: 93%
See 4 more Smart Citations
“…This may be attributed to the adoption of FSAM theory in the model. The other validation of cracking patterns for rectangular RC walls is presented in Figure 11, which shows the comparison of the cracking patterns for specimen J4 [14]. It can be observed that the model is able to predict the global cracking patterns of the specimen.…”
Section: Cracking Patternsmentioning
confidence: 93%
“…Additionally, cracking pattern of the model was extracted from Open Sees to be compared to the tested specimens. The specimens used to validate the results of rectangular RC walls were taken from specimen SW4 [12], SW21 and SW25 [13], and J4 [14]. Furthermore, models for flanged RC walls were taken from specimen J7 [14], and F1 [15].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations